Mimicking lipolytic, adipogenic, and secretory capacities of human subcutaneous adipose tissue by spheroids from distinct subpopulations of adipose stromal/stem cells - Côrtes, Isis; Alves, Gutemberg; Claudio-Da-Silva, Cesar; Baptista, Leandra Santos (Frontiers in Cell and Developmental Biology, 2023)
Background: Adipose tissue engineering may provide 3D models for the understanding of diseases such as obesity and type II diabetes. Recently, distinct ASCs subpopulations were identified from subcutaneous adipose tissue (SAT): superficial (sSAT), deep (dSAT) and the superficial retinacula cutis (sRC). This study aimed to test these subpopulations of adipose stem/stromal cells (ASCs) in 3D spheroid culture induced for adipogenesis under a pro-inflammatory stimulus with lipopolysaccharide (LPS).The samples of abdominal human subcutaneous adipose tissue were obtained during plastic aesthetic surgery (Protocol 145/09).Results: ASC spheroids showed high response to adipogenic induction in sSAT. All ASC spheroids increased their capacity to lipolysis under LPS, however, spheroids from dSAT were higher compared with sSAT (p=0.0045) and sRC (p=0.0005). Newly formed spheroids and spheroids under LPS stimulus from sSAT showed the highest levels of Fatty acid-binding protein 4 (FABP4) and CCAAT/enhancer-binding proteinα (C/EBPα) mRNA expression compared with dSAT and sRC (p<0.0001). ASC spheroids from sRC showed the highest synthesis of angiogenic cytokines such as VEGF compared with dSAT (p<0.0228). Under LPS stimulus, ASC spheroids from sRC showed the highest synthesis of pro-inflammatory cytokines such as IL-6 compared with dSAT (p<0.0092).Distinct physiological properties of SAT can be recapitulated in ASC spheroids. In summary, ASC spheroid from dSAT showed the greatest lipolytic capacity, from sSAT the greatest adipogenic and sRC showed greater secretory capacity when compared to the dSAT. Together, all these capacities make a true mimicry of SAT and hold the potential to contribute for a deeper understanding of cellular and molecular mechanisms in healthy and unhealthy adipose tissue scenarios or in response to pharmacological interventions.